The Validity of Learning Media in the Form of Booklet Types of Pteridophyta (Fern) in the Riverbanks of Wisata Alam Sungai Kembang for Senior High School Grade X - Khairun Nisa; Aulia Ajizah; Sri Amintarti (Master Program of Biology Education, Universitas Lambung Mangkurat, 2021)
Pteridophyta is a sub-concept on Plant (Plantae) material in the Biology subject for Grade X Senior High School. In this competency, students are expected to apply classification principles to classify plants into divisions based on observations of plant morphology and metagenesis and linking their role in the continuity of life on earth. However, most students still find it difficult to understand the concept. This Pteridophyta is due to the lack of local potential-based references that are directly related to student life, one of which is learning media. Learning media is one of the means to help teachers and students learn concepts in Biology more broadly. This encourages researchers to develop learning media in the form of a booklet on the Plantae material sub-concept of ferns (Pteridophyta). This study aims to describe the validity of the booklet developed on the types of ferns (Pteridophyta) on the riverbanks of the Wisata Alam Sungai Kembang. This research uses RandD method with 4D development model to develop learning media in the form of booklets. The results of the validity test of the developed booklet showed very valid results.AbstrakPteridophyta merupakan subkonsep pada materi Tumbuhan (Plantae) di mata pelajaran Biologi SMA Kelas X. Pada kompetensi tersebut siswa diharapkan dapat menerapkan prinsip klasifikasi untuk menggolongkan tumbuhan ke dalam divisio berdasarkan pengamatan morfologi dan metagenesis tumbuhan serta mengaitkan peranannya dalam kelangsungan kehidupan di bumi. Namun kebanyakan siswa masih sulit untuk memahami konsep Pteridophyta tersebut karena masih kurangnya referensi berbasis potensi lokal yang berkaitan langsung dengan kehidupan siswa, salah satunya yaitu media pembelajaran. Media pembelajaran merupakan salah satu sarana untuk membantu guru maupun siswa dalam mempelajari konsep pada Biologi secara lebih luas. Hal tersebut mendorong peneliti untuk mengembangkan media pembelajaran berupa booklet subkonsep tumbuhan paku (Pteridophyta). Penelitian ini bertujuan untuk mendeskripsikan validitas booklet yang dikembangkan tentang jenis tumbuhan paku (Pteridophyta) di bantaran sungai Wisata Alam Sungai Kembang. Penelitian ini menggunakan metode RandD dengan model pengembangan 4D untuk mengembangkan media pembelajaran berupa booklet. Hasil uji validitas terhadap booklet yang dikembangkan menunjukkan hasil sangat valid.